History education and the construction of national identities - Carretero, Mario; Asensio, Mikel; Rodríguez Moneo, María (Emerald Publishing Limited : Information Age Pub., 2012)
How is history represented? As just a record of the past, as a part of a present identity or as future goals? This book explores how historical contents and narratives are presented in school textbooks and other cultural productions (museums, monuments, etc) and also how they are understood by students, in the context of increasing globalization. In these contemporary conditions, the relation between history learning processes, in and out of school, and the construction of national identities presents an ever more important topic. It is being studied by looking at the appropriation of historical narratives, which are frequently based on the official history of a nation state. Most of the chapters in this volume are educational studies about how the learning of history takes place in school settings of different countries such as Canada, France, Germany, Latin America, Spain, the Netherlands, the United Kingdom and the United States. Covering such a broad sample of cultural and national contexts, they provide a rich reflection on history as a subject related to patriotism, cosmopolitanism, both or neither.
Keywords: History -- Study and teaching.; Nationalism and historiography.; National characteristics.; Historicism.; Education -- History.; Teaching of a specific subject.; History of education.; elektronické knihy; electronic books